Hydrolytic Process of Proteins in Moringa oleifera Seeds in Varied Concentrations of Sodium Hydroxide and Hydrochloric Acid - Ika Kurniaty; Ratri Ariatmi Nugrahani; Fatma Sari; Wenny Diah Rusanti; Haryadi Wibowo (Department of Chemical Engineering, Universitas Gadjah Mada, 2020)
Indonesia is endowed with an immense biodiversity that can be used as protein sources. One of these is Moringa oleifera tree that is locally known as Kelor. The seeds of this plant can be used as a protein source, an effective coagulant for water purification, a natural absorbent, and an antimicrobial treatment. Kelor seeds are known to contain fibers, proteins, carbohydrates, and vitamins. The objectives of this study were to identify the optimal solution concentration, determine the yield percentage, and determine the optimal protein content from hydrolytic processes of Moringa seed extraction using Sodium Hydroxide (NaOH) and Hydrochloric Acid (HCl). The hydrolysis took place for 30 minutes at 60oC. The proteins extracted from Moringa seeds were identified with biuret and Braford tests. The NaOH extractions resulted in the highest yield of 12.1% and protein content of 0.43% with 2% NaOH. Whereas those of HCl produced the highest yield of 11.1% and protein content of 9.63% with 1% HCl.